Overexpression of the class I homeodomain transcription factor TaHDZipI‐5 increases drought and frost tolerance in transgenic wheat. Issue 6 (27th December 2017) - Yang, Yunfei; Luang, Sukanya; Harris, John; Riboni, Matteo; Li, Yuan; Bazanova, Natalia; Hrmova, Maria; Haefele, Stephan; Kovalchuk, Nataliya; Lopato, Sergiy
Summary: Characterization of the function of stress‐related genes helps to understand the mechanisms of plant responses to environmental conditions. The findings of this work defined the role of the wheat TaHDZipI‐5 gene, encoding a stress‐responsive homeodomain–leucine zipper class I (HD‐Zip I) transcription factor, during the development of plant tolerance to frost and drought. Strong induction of TaHDZipI‐5 expression by low temperatures, and the elevated TaHDZipI‐5 levels of expression in flowers and early developing grains in the absence of stress, suggests that TaHDZipI‐5 is involved in the regulation of frost tolerance at flowering. The TaHDZipI‐5 protein behaved as an activator in a yeast transactivation assay, and the TaHDZipI‐5 activation domain was localized to its C‐terminus. The TaHDZipI‐5 protein homo‐ and hetero‐dimerizes with related TaHDZipI‐3, and differences between DNA interactions in both dimers were specified at 3D molecular levels. The constitutive overexpression of TaHDZipI‐5 in bread wheat significantly enhanced frost and drought tolerance of transgenic wheat lines with the appearance of undesired phenotypic features, which included a reduced plant size and biomass, delayed flowering and a grain yield decrease. An attempt to improve the phenotype of transgenic wheat by the application of stress‐inducible promoters with contrasting properties did not lead to the elimination of undesired phenotype, apparently due to strict spatial requirements for TaHDZipI‐5 overexpression.